Oil Prices, Exchange Rates and Asset Prices - Marcel Fratzscher; Daniel Schneider; Ine Van Robays (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper takes a financial market perspective in examining the relationship between oil prices, the US dollar and asset prices, and it exploits the heteroskedasticity for the identification of causality in a multifactor model. It finds a bidirectional causality between the US dollar and oil prices since the early 2000s. Moreover, both oil prices and the US dollar are significantly affected by changes in equity market returns and risk. By contrast, oil prices did not react to changes in these financial assets before 2001. The paper provides evidence that this may be explained by the increased use of oil as a financial asset over the past decade, which intensified the link between oil and other assets. The model can account well for the strong and rising negative correlation between oil prices and the US dollar since the early 2000s, with risk shocks and the financialisation process of oil prices explaining most of the strengthening of this correlation.
Keywords: F30; G15; 330; oil prices; asset prices; exchange rates; US dollar; identification; time-varying correlation